Immunity status of invasive pulmonary aspergillosis patients with structural lung diseases in Chinese adults - Liang, Shuo; Jiang, Rong; Lu, Hai-Wen; Mao, Bei; Li, Man-Hui; Li, Cheng-Wei; Gu, Shu-Yi; Bai, Jiu-Wu; Xu, Jin-Fu (Journal of Thoracic Disease, 2017)
Background: Invasive pulmonary aspergillosis (IPA) is a fungal infection frequently observed in patients with immune dysfunction, such as those suffering from structural lung diseases. Nevertheless, studies assessing IPA combined with other common respiratory diseases remain scarce, particularly those regarding the immune status of its patients. Different structural lung diseases are known to differently affect patient immune status; however, the mechanisms by which this is conferred have yet to be determined. Thus, our study aims to compare the immune status of IPA patients with the structural lung diseases chronic obstructive pulmonary diseases (COPD), interstitial lung disease (ILD) and non-cystic fibrosis bronchiectasis (NCFB). Methods: This study was performed retrospectively with data collected over the years 2004 to 2013 at Shanghai Pulmonary Hospital, Tongji University, and included 77 patients whose lower respiratory tract (LRT) samples tested positive for. Our analysis considered blood examinations of CD3+, CD4+, CD8+, CD4+/CD8+, IgG, IgA and IgM levels. Results: CD4+/CD8+ double positive cells, representing cell-mediated immunity, were less abundant in IPA patients with COPD than those with ILD and NCFB (0.81±0.09 vs. 1.39±0.25 and 0.81±0.09 vs. 1.57±0.06, respectively, P